The MUSCLES Treasury Survey. IV. Scaling relations for ultraviolet, Ca ii K, and energetic particle fluxes from M dwarfs - Youngblood, A; France, K; Loyd, R; Brown, A; Mason, J; Schneider, P; Tilley, M; Berta-Thompson, Z; Buccino, A; Froning, C; Hawley, S; Linsky, J; et al. (Institute of Physics, 2017)
Characterizing the UV spectral energy distribution (SED) of an exoplanet host star is critically important for assessing its planet’s potential habitability, particularly for M dwarfs, as they are prime targets for current and nearterm exoplanet characterization efforts and atmospheric models predict that their UV radiation can produce photochemistry on habitable zone planets different from that on Earth. To derive ground-based proxies for UV emission for use when Hubble Space Telescope (HST) observations are unavailable, we have assembled a sample of 15 early to mid-M dwarfs observed by HST and compared their nonsimultaneous UV and optical spectra. We find that the equivalent width of the chromospheric Ca II K line at 3933 Å, when corrected for spectral type, can be used to estimate the stellar surface flux in ultraviolet emission lines, including H I Lyα. In addition, we address another potential driver of habitability: energetic particle fluxes associated with flares. We present a new technique for estimating soft X-ray and >10 MeV proton flux during far-UV emission line flares (Si IV and He II) by assuming solar-like energy partitions. We analyze several flares from the M4 dwarf GJ 876 observed with HST and Chandra as part of the MUSCLES Treasury Survey and find that habitable zone planets orbiting GJ 876 are impacted by large Carrington-like flares with peak soft X-ray fluxes ≥10^− 3W m^−2 and possible proton fluxes ∼10^2–10^3 pfu, approximately four orders of magnitude more frequently than modern-day Earth.